1997
DOI: 10.1183/09031936.97.10020482
|View full text |Cite
|
Sign up to set email alerts
|

The role of pulmonary surfactant in obstructive airways disease

Abstract: Pulmonary surfactant research has an increasing impact on treatment considerations in adult respiratory disorders, above all acute respiratory distress syndrome (ARDS). Obstructive airways diseases have only been sporadically addressed in this respect. In the last decade, direct and circumstantial evidence for surfactant as a contributing factor in the regulation of airway calibre has emerged.Morphologically, a bronchiolar surfactant layer has been demonstrated, whereby the airways are mostly supplied by alveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 104 publications
1
49
0
4
Order By: Relevance
“…В течение последних лет появились сведения о том, что бронхообструкция, вызываемая сокраще нием гладкой мускулатуры бронхов, отек слизистой и повы шенная секреция жидкости в просвет бронхов могут быть час тично обусловлены нарушениями в системе ЛС [53,54,112,113]. Обнаружены изменения в составе ЛС, выделенного из БАЛ больных бронхиальной астмой, и показано, что он обла дает меньшей способностью снижать ПН [22].…”
Section: нарушения состава и свойств легочного сурфактанта при различunclassified
See 2 more Smart Citations
“…В течение последних лет появились сведения о том, что бронхообструкция, вызываемая сокраще нием гладкой мускулатуры бронхов, отек слизистой и повы шенная секреция жидкости в просвет бронхов могут быть час тично обусловлены нарушениями в системе ЛС [53,54,112,113]. Обнаружены изменения в составе ЛС, выделенного из БАЛ больных бронхиальной астмой, и показано, что он обла дает меньшей способностью снижать ПН [22].…”
Section: нарушения состава и свойств легочного сурфактанта при различunclassified
“…Экспериментальные исследования убеждают в обосно ванности попыток сурфактант терапии бронхиальной астмы, однако пока клинические исследования ограничены [23,53,112,165]. S. B. Oetomo и соавт.…”
Section: терапевтическая эффективность препаратов лсunclassified
See 1 more Smart Citation
“…These findings may be due to the inability of the P-V curve to account for complex locoregional heterogeneity in mechanical and airway properties. Conversely, it may be suggested that LVRS, as does bullectomy, allows the decompression of relatively more normal lung areas, and thereby leads to: 1) a recruitment of effective lung volume; 2) a modification of airway geometry that may reduceairway obstruction; and3)an improvement ofsurfactant synthesis in the better inflated, formerly compressed zones, which may also concur with better airway patency [79].…”
Section: Static Mechanics Of the Respiratory Systemmentioning
confidence: 99%
“…Whereas unsaturated PL species are essential to the fluidity of surfactant, the initial formation of the surface film, and the reincorporation of material into the film during expansion in the breathing cycle (1,2,8), they are also distinctively susceptible to oxidation. Surfactant oxidation and dysfunction likely contributes to the pathophysiology of several diseases including adult respiratory distress syndrome (10,11), asthma (12,13), chronic obstructive pulmonary disease (12), and infections (10). In addition to direct effects on the surface properties of surfactant, lipid peroxidation products can inhibit the synthesis and secretion of new surfactant (14) and reduce the viability of alveolar macrophages, and type II pneumocytes (15).…”
mentioning
confidence: 99%